2013
DOI: 10.7708/ijtte.2013.3(2).09
|View full text |Cite
|
Sign up to set email alerts
|

Gender Travel Behaviour and Women Mobility Constraints in Ilesa, Nigeria

Abstract: This paper assessed the gender travel behavior in IIesa, Nigeria. A total of 1,450 copies of a questionnaire were administered to the sampled population in Ilesa, out which 620 men and 580 women completed the questionnaire. Descriptive and inferential statistics were employed for data presentation. The findings revealed that the mean distance traveled to work for men and woman differs in the city. Further analysis revealed that more than 70% of the women depend on public transport for their day-today transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In Pune, Al-Atawi and Saleh (2013) showed that female walking trip shares were 52% higher than men's, 61% higher in Bamako, and a 100% higher in Ashgabat (Al-Atawi and Saleh, 2013). In Tabuk, women tend to have a lower proportion of trips involving personal vehicles like bicycles or personalised motorized modes as it was found in Saleh and Al-Atawi (2015), Train (2003) and Adetunji (2013).…”
Section: Past and Recent Research On Car Sharingmentioning
confidence: 97%
“…In Pune, Al-Atawi and Saleh (2013) showed that female walking trip shares were 52% higher than men's, 61% higher in Bamako, and a 100% higher in Ashgabat (Al-Atawi and Saleh, 2013). In Tabuk, women tend to have a lower proportion of trips involving personal vehicles like bicycles or personalised motorized modes as it was found in Saleh and Al-Atawi (2015), Train (2003) and Adetunji (2013).…”
Section: Past and Recent Research On Car Sharingmentioning
confidence: 97%
“…These needs are often spatially distributed and therefore it is necessary to travel in order to reach them and at the same time selecting the transport mode. A series of different factors still influence the patterns, complexity and frequency of such travelling, including the transport mode choice [9].…”
Section: Theoretical Basis Of Researchmentioning
confidence: 99%
“…These results are similar to IIesa, Nigeria where more than 70 per cent of the women depend on public transport for their day-to-day transactions. Also, 65 per cent of the men depend on their own personal means of transport to commute to different activity centres (Adetunji, 2013). In terms of car-sharing, 30.7 and 41.6 per cent of daughters and wives reported that they use car-sharing to go to work (Table I).…”
Section: General Description Of Survey and Car-sharing In Tabukmentioning
confidence: 99%